Excited states of 90, 92, 94Y populated in 90Zr+208Pb multinucleon transfer reaction. (25th January 2021) - Pajtler, M Varga; Malenica, D Jelavić; Szilner, S; Corradi, L; de Angelis, G; Fioretto, E; Gadea, A; Haas, F; Lunardi, S; Mărginean, N; Mengoni, D; Mijatović, T; et al.
Abstract: Multinucleon transfer reactions in 90 Zr+ 208 Pb have been studied via fragment- γ coincidences, employing the PRISMA magnetic spectrometer coupled to the CLARA γ -array. An analysis on Y isotopes has been carried out incorporating spectroscopic as well as reaction mechanism aspects. New γ transitions have been observed in 94 Y, confirming the findings of recent studies where nuclei were produced via fission of uranium, and a comparison with near-by 90, 92 Y isotopes populated in the same reaction has been discussed. Experimental cross sections have been extracted and compared with the GRAZING calculations, showing a fair agreement along the neutron pick-up side. The results confirm how multinucleon transfer reactions are a suitable mechanism for the study of neutron-rich nuclei.